Genetic and environmental factors contribute to variation in cell wall composition in mature desi chickpea (Cicer arietinum L.) cotyledons. (27th April 2018) - Wood, Jennifer A.; Tan, Hwei‐Ting; Collins, Helen M.; Yap, Kuok; Khor, Shi Fang; Lim, Wai Li; Xing, Xiaohui; Bulone, Vincent; Burton, Rachel A.; Fincher, Geoffrey B.; Tucker, Matthew R.
Abstract: Chickpea ( Cicer arietinum L.) is an important nutritionally rich legume crop that is consumed worldwide. Prior to cooking, desi chickpea seeds are most often dehulled and cleaved to release the split cotyledons, referred to as dhal. Compositional variation between desi genotypes has a significant impact on nutritional quality and downstream processing, and this has been investigated mainly in terms of starch and protein content. Studies in pulses such as bean and lupin have also implicated cell wall polysaccharides in cooking time variation, but the underlying relationship between desi chickpea cotyledon composition and cooking performance remains unclear. Here, we utilized a variety of chemical and immunohistological assays to examine details of polysaccharide composition, structure, abundance, and location within the desi chickpea cotyledon. Pectic polysaccharides were the most abundant cell wall components, and differences in monosaccharide and glycosidic linkage content suggest both environmental and genetic factors contribute to cotyledon composition. Genotype‐specific differences were identified in arabinan structure, pectin methylesterification, and calcium‐mediated pectin dimerization. These differences were replicated in distinct field sites and suggest a potentially important role for cell wall polysaccharides and their underlying regulatory machinery in the control of cooking time in chickpea. Abstract : Natural variation in cotyledon composition, polysaccharide content, and structure was identified in distinct desi chickpea genotypes grown in different field sites. These differences suggest a potentially important role for cell wall polysaccharides and their underlying regulatory machinery in the control of cooking time in chickpea.